POLICY TOWARDS PERPETRATORS OF MILD CRIMES THROUGH A RESTORATIVE JUSTICE APPROACH - Herlambang harjo semedy; Sunardi; Suratman (International Journal of Cultural and Social Science, 2025)
This research examines the application of restorative justice in handling minor crimes in Indonesia as an alternative to the retributive approach in the criminal justice system. Using a descriptive qualitative method with a juridical-sociological approach, this study includes literature reviews, policy analysis, and interviews with law enforcement officials and minor offenders. The findings indicate that restorative justice contributes positively by accelerating case resolution, reducing recidivism, and restoring social relationships between offenders, victims, and the community. However, its implementation faces challenges such as limited human resources, uneven understanding among officers, and the lack of clear standard operating procedures. The implications of this research emphasize the need for criminal policy reform based on local values and strengthening the capacity of law enforcement officers to implement restorative justice nationwide.